Effects of Second Screening: Building Social Media Social Capital through Dual Screen Use. (19th March 2019) - Huber, Brigitte; Gil de Zúñiga, Homero; Diehl, Trevor; Liu, James
Abstract: Second screening politics is an emerging communication practice for engaging with public affairs content. Scholars are increasingly interested in exploring pro-democratic effects of dual screening during news events and election cycles. This paper examines the potential for second screening practices to develop social capital on social media platforms through online and offline political discussion: a key component of maintaining social resources. More specifically, this manuscript focuses on the development of community-related social capital. Relying on two waves of panel data from 19 countries, the results suggest that dual screening contributes to the proliferation of building social capital on social media over time. This relationship is also partially mediated through online political discussion. Moreover, the between-country variation in the relationship between second screening and social media social capital is related to country-level freedom of expression indicators.